From Co-occurrence to Configuration: The Demonstration-Imitation Cycle in Grade VII Fiqh Instruction at an Indonesian Madrasah Tsanawiyah - Fran Ario Wardhana; M. Thontawi; Yanri Ramdhano; Ismail Fahri; Sachrawi Hidayat; Nikmatuz Zaifa (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
Fiqh instruction at the Madrasah Tsanawiyah (MTs) level combines legal knowledge with ritual practice, yet teacher-centered lecture dominates the classroom. Demonstration combined with concrete media has been proposed as an alternative, but prior research treats the two as concurrent additions rather than a single configuration. This qualitative case study examines this integration in a seventh-grade fiqh class at MTs Al-Irsyad, Kuala Jambi, asking how it takes shape, what conditions facilitate or hinder it, and how it is sequenced within the lesson. Data were collected through semi-structured interviews with 11 participants: the principal, two fiqh teachers, three teachers of other subjects, and five seventh-grade students. Observation of three sessions, and document analysis, with two-cycle coding and trustworthiness supported by triangulation, member checking, audit trails, and reflective notes. Integration occurred at three points of method-media convergence: preparatory, demonstrative, and evaluative, forming an interlinked configuration and a recurrent demonstration-imitation cycle in which teachers modeled a step before students imitated it. Feasibility depends on leadership support, media availability, teacher competence, and student receptiveness, and is limited by time constraints, inadequate media, and uneven attention. Teachers implement this configuration through a stable three-phase sequence: preparation, demonstration, and evaluation, whose weights vary with procedural complexity; segmented cycles and matched assessment characterize the most successful sessions. These findings reframe the demonstration-and-media pairing as a deliberate configuration and identify a micro-mechanism integrating observational and experiential learning, with implications for fiqh teacher training and lesson design